Ascorbic acid as an effective antioxidant additive to enhance the efficiency and stability of Pb/Sn-based binary perovskite solar cells. (April 2017) - Xu, Xiaobao; Chueh, Chu-Chen; Yang, Zhibin; Rajagopal, Adharsh; Xu, Jingqi; Jo, Sae Byeok; Jen, Alex K.-Y.
Abstract: Realizing efficient organic/inorganic hybrid perovskite solar cells (PVSCs) with reduced toxic lead (Pb) content is important for developing sustainable clean photovoltaics. The vigorous progress made recently for tin (Sn)- and Pb/Sn-based PVSCs has drawn considerable attention because of their potential to reduce Pb content in perovskites. However, the inferior chemical stability of Sn to Pb element necessitates more sophisticated morphological and processing engineering of Sn-containing PVSCs in order to achieve high performance and stability. We have recently discovered that ascorbic acid (AA) can serve as a simple but effective additive to simultaneously enhance the performance and stability of Sn-containing PVSCs. It is revealed that AA as a commonly known antioxidant can retard the oxidation of Sn-containing precursor solution of perovskite while modulate its perovskite crystallization by forming intermediate complexes. This is evidenced by the prolonged photogenerated carrier lifetime (182.7 ns) of its derived MA0.5 FA0.5 Pb0.5 Sn0.5 I3 film. As a result, a high PCE of 14.01% with improved stability can be realized in the binary metal PVSC with AA as additive, outperforming the value (12.18%) of the control device processed with the regular SnF2 additive. Graphical abstract: Ascorbic acid was for the first time introduced as an effective antioxidant additive to enhance the efficiency and stability of Sn-based perovskite solar cells. It not only can effectively hinder the precursor solution of Sn-based perovskite from oxidation but modulate the Sn-based perovskite crystallization via forming associated intermediate complexes. A high PCE of 14.01% with improved stability can be finally realized in a MA0.5 FA0.5 Pb0.5 Sn0.5 I3 PVSC processed with AA additive, outperforming the value (12.18%) of the control device processed with the regular SnF2 additive. Highlights: For the first time, a common antioxidant, ascorbic acid (AA), is introduced as an additive to assist the processing of Sn-containing perovskites. The photogenerated carrier lifetime in MA0.5FA0.5Pb0.5Sn0.5I3 film processed with AA additive is almost 2 times longer (182.7 ns) than that (92.5 ns) in MA0.5FA0.5Pb0.5Sn0.5I3 film with SnF2. For best of our knowledge, this is the highest value reported for Sn-based perovskite family. A high PCE of 14.01% with improved stability can be realized in a MA0.5FA0.5Pb0.5Sn0.5I3 perovskite solar cell (PVSC) processed with AA additive, outperforming the value (12.18%) of the control device processed with the regular SnF2 additive. AA-derived PVSC can preserve 99% of its initial PCE after being stored in glovebox for 1 month, whilst SnF2-derived device only has 63% of its initial value remained.